Assessing the Efficiency and Challenges of Online Single Submisson in Improving Public Services - Sakawati, Herlina; Yamin, Muh. Nur; Sulmiah, Sulmiah; Widyawati, Widyawati; Fitri, Anisa (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study examines the implementation of the Online Single Submission (OSS) system in East Luwu Regency to improve the quality of public services, especially in licensing services, using descriptive qualitative. The research data used came from interviews, observations, and literature reviews. The research findings show that OSS has improved service efficiency in terms of ease of access, speed, and user experience. However, there are still challenges, especially related to unstable internet infrastructure, lack of complete information, and system integration problems. To maximize the potential of OSS, it is necessary to improve technology infrastructure and improve communication strategies. This study provides insight into the need for a more comprehensive digital service framework to ensure equitable access and user satisfaction in the provision of public services.